Simulated surgery of single-port robotic transanal total mesorectal excision: a case study - He Kuan; Xu Zhou; Shen Haode; Zheng Huichao; Du Jing; Xu Kun; Tong Weidong; Wu Yi; Li Fan (结直肠肛门外科)
Surgical simulators offer surgeons the opportunity to practice surgical procedures in a simulated environment, while single-port robotic surgical system provide a platform with exceptional operational flexibility and precision. Our research team constructed a visualized solid model of complete male pelvic structure based on the Chinese Visible Human datasets, incorporating 3D printing technology. This study reports on the practical effects of performing simulated surgery of transanal total mesorectal excision (taTME) using a single-port robotic surgical system (EDGE SP1000) on this model. The aim is to provide a reference for optimizing simulation training methods and improve the technical training system for this surgical procedure, while also laying a theoretical and practical foundation for the clinical application of the EDGE SP1000 in taTME.